En enhanced matrix-free method via double step length approach for solving systems of nonlinear equations - Sani Halilu, Abubakar; Abdullahi, H.; Yusuf Waziri, Mohammed (International Journal of Applied Mathematical Research, 2017)
A variant method for solving system of nonlinear equations is presented. This method use the special form of iteration with two step length parameters, we suggest a derivative-free method without computing the Jacobian via acceleration parameter as well as inexact line search procedure. The proposed method is proven to be globally convergent under mild condition. The preliminary numerical comparison reported in this paper using a large scale benchmark test problems show that the proposed method is practically quite effective.